Genetic background of the rare Yus and Gerbich blood group phenotypes: homologous regions of the GYPC gene contribute to deletion alleles. (8th March 2017) - Gourri, Elise; Denomme, Gregory A.; Merki, Yvonne; Scharberg, Erwin A.; Vrignaud, Cedric; Frey, Beat M.; Peyrard, Thierry; Gassner, Christoph
Summary: The GYPC gene encodes the glycophorins C and D. The two moieties express 12 known antigens of the Gerbich blood group system and functionally stabilize red blood cell membranes through their intracellular interaction with protein 4.1 and p55. Three GYPC exon deletions are responsible for the lack of the high‐frequency antigens Ge2 (Yus type, exon 2 deletion), Ge2 and Ge3 (Gerbich type, exon 3 deletion), and Ge2 to 4 (Leach type, exons 3 and 4 deletion), but lack exact molecular description. A total of 29 rare blood samples with Yus (GE:‐2, 3, 4) and Gerbich (GE:‐2, ‐3, 4) phenotypes, including individuals of Middle‐Eastern, North‐African or Balkan ancestry were examined genetically. All phenotypes could be explained by 4 different Yus alleles, characterized by deletions of exon 2 and adjacent introns, and 3 different Gerbich alleles, with deletions of exon 3 and adjacent introns. A 3600 base pair GYPC region, encompassing exon 2 and flanking region, shares a high degree of sequence homology with a region flanking exon 3, probably representing an evolutionary duplication event. Defining the expression of Gerbich variants presently relies on rare serological reagents. Our approach substitutes the serological characterization with a precise genotype approach to identify the rare Yus and Gerbich alleles.